The Potential of Wind and Solar Energy in Malaysia East Coast: Preliminary Study at Universiti Malaysia Pahang (UMP) - M. M., Noor; K., Kadirgama; A. K., Amiruddin; K. V., Sharma (2011)

(untitled)
The main objective of this article is to investigate wind and solar potential in Universiti Malaysia Pahang renewable energy resources as response to Malaysian government regarding to green technology. It is a preliminary study mainly focuses on technique of measurement and collecting potential wind and solar data. The first solar panels installation was planned to be inside Universiti Malaysia Pahang with the first wind turbine being installed at the bank of the Sungai Pahang in Pekan, Pahang. The local solar radiation regime was described with on-site measurements and calculations where the former was carried out from the beginning of 2010. The setup of the measurement device is discussed in this paper.